A deep learning method for fog removal in image - Guo, Dongfang (2019)
Fog removal has always been a vital issue in image and video processing. With the development of various vision-based applications (e.g. photography, video surveillance and autonomous driving), images and videos are of essential importance to extract useful scene information. However, real-world scenes are sometimes obscured by fog, suffering from degraded visibility, color distortion and low contrast. Therefore, fog removal is significant mean in real-world image pre-processing for many vision tasks.